Forces of change : new strategies for the evolving health care marketplace - Shore,David A.; Shore, David A. (San Francisco : Jossey-Bass, 2012)
"This groundbreaking book is based on an innovative model developed by David Shore that serves as the foundation for his Forces of Change program. Forces of Change offers an invaluable guide and sourcebook for the latest thinking on how organizations and their leaders can navigate an ever-changing health care marketplace. The book's emphasis on creating competitive advantage and developing implementation strategies could scarcely be more timely or more in demand"--
Machine generated contents note: Editor's PrefaceDavid A. Shore, Harvard School of Public HealthAcknowledgmentsThe EditorThe ContributorsPART I: Can We Get Better?1. Framing the Forces of Change (David A. Shore)2. The Market Dynamics of Health Care (Eric D. Kupferberg, Northeastern University, Harvard School of Public Health)3. Transformational Leadership: The Key to Success (Michael J. Dowling, North Shore-LIJ Health System, Harvard School of Public Health)PART II: The Elements of Change4. Employee Engagement and the Transformation of the Health Care Industry (Max Caldwell and Towers Watson)5. Patient Safety in the Era of Health Care Reform (Lucian Leape, Harvard School of Public Health)6. Health Care Reform and Technological InnovationDavid Shoultz, Philips Healthcare7. Health Care IT: A Critical Enabler for Health Care Transformation (John P. Glaser, Siemens Healthcare)8. Health Care IT: A Reality Check (Ashish K. Jha, Harvard School of Public Health)9. A Systematic Solution: Integrated Health Care Management (Jeff Margolis, The TriZetto Group)PART III: Reshaping the Organization10. Stakeholder Interactions: Can We Transform Bad Behavior? (Eric D. Kupferberg)11. The Trust Prescription: How Health Care Organizations Can Win the Confidence and Compliance of Their Key Stakeholders (David A. Shore)12. A Winning Brand: Leveraging the Power of Intangible Assets (David A. Shore)13. Implementing Health Care Change through Projects (David A. Shore)EndnotesIndex.
Includes bibliographical references and index.
Keywords: Health care reform -- United States; Medical policy -- United States; Medical economics -- United States; MEDICAL / Public Health